The enhanced effect of oxalic acid on the electroreduction of Cr(VI) via formation of intermediate Cr(VI)-oxalate complex. Issue 4 (10th February 2020) - Liu, Yijie; Xin, Shuaishuai; Jiang, Bo
ABSTRACT: In this study, the enhanced effect of oxalic acid (Ox) on Cr(VI) electroreduction was evaluated. It was found that for Cr(VI)-contaminated solution ([Cr(VI)]0 = 1.0 mM, pH = 3.0), addition of 5.0 mM Ox can significantly increase Cr(VI) reduction from 0.36 to 1.0 mM within 90 min electrolysis reaction, accompanying with the increase of current efficiency from 19% to 53%. Increasing initial Ox concentration (0–10 mM) and electric current (10–40 mA) facilitated Cr(VI) reduction, whereas it was inhibited with decreasing solution pH value (2.0–3.5) and elevating Cr(VI) concentration (0.1–2.0 mM), respectively. Results show that reactive electron was the primary reductant for the heterogeneous reduction of Cr(VI) on the cathode. In addition, Ox can also serve as an electron donor for the homogeneous reduction of Cr(VI). During this process, the formation of Cr(VI)-oxalate complex is indispensable for the enhanced Cr(VI) reduction. The coordination of Ox with Cr(VI) did not only make the structure of Cr(VI) more distorted but also improved the reactivity of Cr(VI) in Cr(VI)-oxalate complex toward reduction reaction. In general, this study provides an energy-efficient and environmentally benign strategy for the treatment of Ox and Cr(VI) co-contaminated wastewater. GRAPHICAL ABSTRACT: